UPAYA MENINGKATKAN HASIL BELAJAR IPAS MATERI DAERAH KEBANGGAANKU KELAS 5 MELALUI METODE DISKUSI KELOMPOK DENGAN BERBANTUAN MEDIA JEMURAN GEMBIRA DI SDN METESIH 03 MADIUN - Mohamad Fatikh Prasmadhita; Hendra Mushtofa Muzammil Wafy; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to help fifth-grade students at SDN Metesih 03 Jiwan, Madiun Regency, learn better by using group discussion techniques and Jemuran Gembira media with the theme "My Proud Region". This research was motivated by the fact that monotonous, repetitive, and boring learning approaches lead to low student learning outcomes. This study is a Classroom Action Research (CAR) conducted in two cycles. This study follows the Kemmis and McTaggart paradigm, which has four steps: planning, action implementation, observation, and reflection. Eight fifth-grade students were selected as research subjects. We used tests, documentation, and observation to collect data. The results showed that students' cognitive, emotional, and psychomotor abilities improved significantly. The average score increased to 70 in the first cycle, and the passing percentage increased to 58%, but the success indicator had not been achieved. After the changes were made in Cycle II, learning outcomes improved significantly. The average score became 91.25, and all students were declared to have passed. This improvement was also aided by students who were more interested and motivated. Thus, using clotheslines and group discussions can help elementary school children learn more about science. This strategy is offered as a fun and relevant alternative to thematic teaching.